2020
DOI: 10.1371/journal.pone.0235142
|View full text |Cite
|
Sign up to set email alerts
|

Risk of intestinal and extra-intestinal cancers in patients with inflammatory bowel diseases: A population-based cohort study in northeastern Italy

Abstract: The cancer risk of patients with inflammatory bowel diseases (IBD) has not been well documented in southern Europe. This study aimed to evaluate the overall pattern of cancer risk among patients with IBD in Friuli Venezia Giulia, northeastern Italy. A population-based cohort study was performed through a record linkage between local healthcare databases and the cancer registry (1995-2013). We identified 3664 IBD patients aged 18-84 years, including 2358 with ulcerative colitis (UC) and 1306 with Crohn's diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 47 publications
2
27
0
1
Order By: Relevance
“…Thus, thyroid is also not ignored in IBD surveillance. And an elevated risk of kidney cancer in our data was consistent with a cohort study in northeastern Italy by Taborelli et al 30 . The reported possible mechanisms involves the increased occurrence of chronic kidney disease 31 or potential nephrotoxic drugs such as thiopurines 32 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, thyroid is also not ignored in IBD surveillance. And an elevated risk of kidney cancer in our data was consistent with a cohort study in northeastern Italy by Taborelli et al 30 . The reported possible mechanisms involves the increased occurrence of chronic kidney disease 31 or potential nephrotoxic drugs such as thiopurines 32 …”
Section: Discussionsupporting
confidence: 92%
“…Taborelli et al 30 The reported possible mechanisms involves the increased occurrence of chronic kidney disease 31 or potential nephrotoxic drugs such as thiopurines. 32 Specifically, in our study, the increased risk of malignancies in UC patients mainly concentrated on young and middle-aged patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of two included studies that stratified for disease extent at diagnosis demonstrated that those with colonic disease location had a SIR of 4.3 (2.0–9.4) [14], comparable to the SIR found in the present study. In contrast, a recent population‐based cohort study from Italy showed no increased risk of CRC in a group of 1306 patients with CD [8]. A nationwide cohort study from Denmark following 14,463 CD patients published in 2012 reported a relative risk of 0.85 (95% CI 0.67–1.07) compared with the general population [5].…”
Section: Discussionmentioning
confidence: 99%
“…CD patients are more likely to develop extraintestinal malignancies than UC patients. Upper GI cancer, lung cancer, urinary bladder cancer, skin squamous cell cancer, breast cancer were more frequent among CD patients and liverbiliary cancer, leukaemia, breast cancer and corpus uteri cancer among UC patients (5,13,14).…”
Section: Introductionmentioning
confidence: 94%
“…Ulcerative colitis (UC) and Crohn's disease (CD) are life long diseases with a chronic inflammation of the gast rointestinal (GI) tract. Patients with inflammatory bowel disease (IBD) have an increased risk to develop malig nant neoplasms, particularly colorectal cancer (CRC) in ulcerative colitis and colon Crohn's disease because of the chronic intestinal inflammation, however recent stu dies suggest the rate is decreasing thanks to improved surveillance (1)(2)(3)(4)(5)(6)(7). Colorectal cancer is the third most common cancer worldwide and accounts for 1015% of all deaths in IBD (8).…”
Section: Introductionmentioning
confidence: 99%